2009
DOI: 10.1002/ijc.24675
|View full text |Cite
|
Sign up to set email alerts
|

Id‐1 promotes tumorigenicity and metastasis of human esophageal cancer cells through activation of PI3K/AKT signaling pathway

Abstract: Id-1 (inhibitor of differentiation or DNA binding) is a helix-loophelix protein that is overexpressed in many types of cancer including esophageal squamous cell carcinoma (ESCC). We previously reported that ectopic Id-1 expression activates the phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT) signaling pathway in human esophageal cancer cells. In this study, we confirmed a positive correlation between Id-1 and phospho-AKT (Ser473) expressions in ESCC cell lines, as well as in ESCC on a tissue microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 43 publications
6
84
1
Order By: Relevance
“…19,20,34,48 Recent studies have also shown that the in vitro proliferation of ESCC cell lines was reduced by inhibition of PI3K or MEK1/2. 49,50 Here we demonstrated that GDF15 increased the growth of ESCC cell lines dose-dependently. Moreover, this study is the first to report that both the Akt and Erk1/2 pathways with the induction of proliferation were activated by GDF15 in ESCC cell lines and that treatment with a MEK1/2 inhibitor (PD98059) and a PI3K inhibitor (LY294002) abolished the growth of ESCC cell lines.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 63%
“…19,20,34,48 Recent studies have also shown that the in vitro proliferation of ESCC cell lines was reduced by inhibition of PI3K or MEK1/2. 49,50 Here we demonstrated that GDF15 increased the growth of ESCC cell lines dose-dependently. Moreover, this study is the first to report that both the Akt and Erk1/2 pathways with the induction of proliferation were activated by GDF15 in ESCC cell lines and that treatment with a MEK1/2 inhibitor (PD98059) and a PI3K inhibitor (LY294002) abolished the growth of ESCC cell lines.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 63%
“…It has also been reported that nicotine can induce the Akt pathway, and Akt has been shown to elevate the levels of ID1 (29); the phosphatidylinositol 3-kinase (PI3K) Akt pathway also intersects with Src kinase activity. To examine whether the PI3K/Akt pathway contributes to nicotine-mediated induction of ID1, A549 cells were rendered quiescent and stimulated with 1 M nicotine in the presence of 1 M Src inhibitor PP2 or PI3K inhibitor LY294002 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…INPP5J, a member of the 5-phosphatase family, has been recently demonstrated to function as a vital negative regulator of PI3K/ Akt signalling 12 , which is constitutively activated in numerous types of human cancers, including ESCC 26 . However, the clinical significance and biological role of INPP5J in ESCC remain unknown.…”
Section: Resultsmentioning
confidence: 99%